Modernidade, colonialidade e os corpos indesejáveis: o genocídio negro no Brasil - Bezerra, Carina Felix (2021)
This study brings a discussion about the genocide of the black population in Brazil, based on the murders committed by the Military Police, as Public Security professionals in the State. I assume that the forms of racism built in the colonization process and in the beginning of modernity, with the objective of dominating the bodies and minds of African peoples, are still present in the contemporary world and create bases to provide for the phenomenon of black genocide in the country. In this context, the blacks are understood as dangerous and undesirable bodies, therefore, subject to extermination. The objectives that guided this research were: to analyze the dynamics of the Brazilian black genocide project, based on cases of homicides committed by police officers; to discuss the construction of different expressions of racism in Brazil from the idea of modernity and coloniality; to approach the role of the State in black genocide from an empirical basis made in the district of Ibura, and to analyze three cases of murders of black youths committed by police officers, based on the discourse of the media and on the families of the victims present in the news reports and publications journalistic. The research follows the decolonial thinking and stands out for being qualitative in nature, consisting of a bibliographic, field and documentary research, as I use analysis of reports, journalistic notes, images, such as photos, paintings, murals and accusations. The results showed that there is an ongoing black genocide project in the country and that the Police are one of the State's instruments for this purpose, while continuing with its violent actions directed at the poor, black and peripheral population, even if some of them are just children.